Cybernetic approach to solving the task of database reengineering - Есин, В.И. (Radiotekhnika, 2017)
The task of reengineering databases of the organizational management information system is formulated and formalized in the form of the structural adaptation task known from the general adaptive systems theory. The method for its solution is proposed.